The Influence of Forests on Climate - Warren, W. D. M. (Indian Forester, 1941)
The influence of forests on the local (micro) climate has been scientifically proved from ground meteorological data. Certain indisputable climatic Laws have been enunciated explaining why this happens. Deductions from upper air observations are liable to serious error, and cannot upset these facts. More research is required to prove how far the climatic influence extends beyond the forest edge.